Media Animaker dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Sekolah Dasar - Mersi Febriyanti; Sri Erdawati (Institut Agama Islam Hidayatullah Batam, 2025)
Low student learning outcomes are caused by boredom, not paying attention to the material and not being able to explain the material being taught, and not responding to teacher questions. The goal to be achieved is to find out the application of animaker media in improving student learning outcomes in Elementary Schools. Kemmis and MC Tagart Classroom Action Research (PTK) was carried out in 2 cycles, each cycle consisting of 3 meetings with the following stages: planning, implementation, observation, and reflection. The subjects of the study were 26 fourth grade students. While the objects of the study were Animaker Media and student learning outcomes. The results showed an increase from 46.15% (quite good), increasing to 61.53% (good), and finally to 80.76% (good). It is concluded that animaker media can improve the learning outcomes of Elementary School students.